A comparison of AMT strategies in the USA, South Africa and Germany. (1st January 2002) - Orr, Stuart
This paper presents a comparison of the findings of three surveys of AMT adoption, independently carried out in the USA, South Africa and Germany. It was found that in both South Africa and Germany the greatest number of respondents claimed that their ideas for AMT implementations came from the Production Department, whilst the greatest number of US respondents identified the Engineering Department. The US respondents involved greater numbers of levels of management and functional areas in the planning process and utilised more financial evaluation techniques in assessment. At the time, the USA was rated as the most competitive industrialised nation and the best performing industrialised nation with regard to technology management.